2013
DOI: 10.4269/ajtmh.13-0006
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infections among Long-Term-Residents and Settled Immigrants in Qatar in the Period 2005 to 2011

Abstract: Abstract. The expanding economy of Qatar in the last two decades has attracted immigrants, often from countries with poor socio-economic levels. Many arrive with patent intestinal parasitic infections, and recent analyses have indicated consistently rising trends in the prevalence of some infections. Here, we examined 18,563 hospital records of subjects in Qatar seeking medical assistance for a variety of ailments, combining data from 2009 to 2011 with the earlier dataset from 2005 to 2008 to enable trends to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 15 publications
4
31
1
1
Order By: Relevance
“…This prevalence is slightly higher than that reported in expatriates working in Saudi Arabia (14.9%) in 2013 [41]. In other studies in the UAE [40], Saudi Arabia [41], and Qatar [42], the IPs prevalence dropped to less than 10%, in long-term residents and expatriates. It is important to note there are foci in Saudi Arabia [27], Oman [43], and Yemen [44] that have a higher incidence of IPs naturally when compared to other parts of these countries.…”
Section: Discussioncontrasting
confidence: 53%
“…This prevalence is slightly higher than that reported in expatriates working in Saudi Arabia (14.9%) in 2013 [41]. In other studies in the UAE [40], Saudi Arabia [41], and Qatar [42], the IPs prevalence dropped to less than 10%, in long-term residents and expatriates. It is important to note there are foci in Saudi Arabia [27], Oman [43], and Yemen [44] that have a higher incidence of IPs naturally when compared to other parts of these countries.…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast to the values for prevalence of helminths among long-term residents recorded in the period from 2005 to 2008, in subsequent years (2009–2011) a clear trend of declining prevalence was observed, but even so, subjects from western Asia, including Nepal, still showed the highest prevalence of helminth infections [12]. In the most recent analysis of infections among long-term residents (including 2012–2014), prevalence of helminth infections was found to have continued to fall even further and the distinction between residents from western Asia and other regions had become less obvious [10].…”
Section: Discussionmentioning
confidence: 96%
“…In our earlier analyses of the prevalence of parasitic infections and their temporal trends among settled immigrants in Qatar [12], immigrants from western Asia were observed to harbor the highest prevalence of helminth infections whereas immigrants from most other regions lost their helminth burdens almost completely after acquiring residency permits. Given the huge numbers of immigrants from western Asian countries and the persistence of helminth infections among the Nepalese in particular, our findings were of some concern with respect to public health in Qatar and this was the intended focus of the current project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are important to the public health in the country, particularly in the food industry. In a follow-up study, Abu-Madi, Behnke, and Doiphode (2013) found that all prevalence values for the period 2009e2011 were numerically lower than those recorded for 2005e2008. Combined intestinal protozoan infections fell from 8.0% to 5.3%, and combined helminth infections fell from 2.6% to 1.9%.…”
Section: Gastrointestinal Diseasesmentioning
confidence: 86%